AN OBSERVATIONAL STUDY ON THE PROFILE OF PSYCHIATRIC DISORDERS IN ELDERLY PATIENTS ATTENDING PSYCHIATRY OPD IN A TERTIARY HEALTH CARE CENTRE (Asian Journal of Medical Research and Health Sciences, 2026)
Introduction: The global increase in life expectancy has led to a growing elderly population, accompanied by a rising burden of psychiatric disorders. Mental health problems among older adults are often under-recognized because of various social factors, and limited access to specialized geriatric mental health services, particularly in low- and middle-income regions. Data on the pattern of psychiatric morbidity among the elderly in North-East India remain limited. This study aimed to evaluate the pattern and distribution of psychiatric disorders among elderly patients attending the psychiatry outpatient department of a tertiary care centre in North-East India. Methods: This hospital-based cross-sectional observational study included 100 patients aged 60 years and above attending the psychiatry outpatient department of a tertiary care hospital. Psychiatric diagnoses were made according to DSM-5 criteria after detailed clinical evaluation, and socio-demographic variables were recorded. Results: Schizophrenia spectrum and other psychotic disorders were the most common diagnoses, affecting 28% of participants. Bipolar and related disorders and major and mild neurocognitive disorders were each observed in 18% of cases. Depressive disorders were observed in 14% of patients, while anxiety disorders were identified in 9%. Certain diagnostic categories were more frequently observed among financially dependent individuals, and variations were noted across rural and urban populations. Conclusion: The study highlights a substantial burden of psychiatric morbidity among elderly patients attending tertiary psychiatric outpatient services and underscores the need for early identification, tailored interventions, and comprehensive mental health support systems for the geriatric population.